Donor assistance and urban service delivery in Africa - Richard Stren (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Sub-Saharan African cities have been growing at historically unprecedented rates. Since the early 1970s, they have welcomed international assistance involving a succession of major thematic objectives. The main agency involved in urban assistance has been the World Bank. But as its goals have changed, it has been obliged to operate increasingly through a decentralized, more democratically structured local government system. Overall, the success of this international assistance regime has been positive but modest, given the overwhelming needs of African cities. Still, African cities are increasingly finding solutions both co-operatively and on their own.
Keywords: F35; H70; N47; O18; 330; urban assistance; African cities; decentralization; World Bank; local government; urban management; Entwicklungshilfe; Kommunalverwaltung; Kommunale Dienstleistung; Afrika südlich der Sahara